Automotive electricity : electric drives - Beretta, Joseph (London : ISTE Ltd ; Hoboken, NJ : J. Wiley, 2010)
"Since the beginning of the century, electrical engineering technologies and applications have pervaded daily life and are present in the majority of everyday products, tools, and appliances. Increasingly these applications are becoming more prevalent in the automotive vehicle and products market. While change in this field has been relatively slow over the last ten years, the pace of change is now beginning to accelerate and we are witnessing a wave driven by regulatory constraints and market laws which are sweeping away the last bastions of resistance." "This book discusses both the historical and scientific issues surrounding the application of electrical technology in the automotive drives field, as well as potential future developments, such as hybrid vehicles and fuel cells. In the current context of energy conservation, pollution prevention, and carbon control, this book will provide an important and timely examination of a potentially enormous new market."--Jacket
Introduction / Joseph Beretta -- Basic definitions / Joseph Beretta -- Electric-powered vehicles / Joseph Beretta, Cyriacus Bleijs, Franc̦ois Badin and Thierry Alleau -- The components of electric-powered vehicles / Joseph Beretta, Jean Bonal and Thierry Alleau -- Prospects and evolutions of electric-powered vehicles: what technologies by 2015? / Joseph Beretta.
Includes bibliographical references and index.
Translated from the French.
Print version record.
Keywords: Electric automobiles -- Motors; Electric automobiles -- Electric equipment; Electric driving; Automobiles électriques -- Moteurs; Automobiles électriques -- Équipement électrique.; Commande électrique.; Electric driving